2012
DOI: 10.1371/journal.pone.0049947
|View full text |Cite
|
Sign up to set email alerts
|

On the Contribution of Binocular Disparity to the Long-Term Memory for Natural Scenes

Abstract: Binocular disparity is a fundamental dimension defining the input we receive from the visual world, along with luminance and chromaticity. In a memory task involving images of natural scenes we investigate whether binocular disparity enhances long-term visual memory. We found that forest images studied in the presence of disparity for relatively long times (7s) were remembered better as compared to 2D presentation. This enhancement was not evident for other categories of pictures, such as images containing car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
0
12
2
Order By: Relevance
“…The results of Experiment 1 seem to indicate that binocular disparity does not contribute to the fast recognition of visual scenes, if anything, a nonsignificant trend for worse recognition of stereo pictures emerged, a result which is strikingly different from the observation of Liu and colleagues (2000), who found that stereo produced a small (2.5%) enhancement in the recognition rate of faces with a viewing time of 1.5 s and the observation of Valsecchi and Gegenfurtner (2012), who found a significant improvement in the long-term memorization rate when observers viewed the same forest pictures for 7 s.…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…The results of Experiment 1 seem to indicate that binocular disparity does not contribute to the fast recognition of visual scenes, if anything, a nonsignificant trend for worse recognition of stereo pictures emerged, a result which is strikingly different from the observation of Liu and colleagues (2000), who found that stereo produced a small (2.5%) enhancement in the recognition rate of faces with a viewing time of 1.5 s and the observation of Valsecchi and Gegenfurtner (2012), who found a significant improvement in the long-term memorization rate when observers viewed the same forest pictures for 7 s.…”
Section: Discussioncontrasting
confidence: 76%
“…The pictures were taken in the Schiffenberger Wald, in the vicinity of Giessen, using a Fujifilm Finepix W1 3D digital camera (Fujifilm Holdings Corporation, Tokyo, Japan). A subset of the images was used by Valsecchi and Gegenfurtner (2012). In the present and in the following experiments, the images were displayed in a mirror stereoscope.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations